2019
DOI: 10.1002/mgg3.985
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of diabetic kidney disease: A follow‐up study in the Arab population of the United Arab Emirates

Abstract: BackgroundTwo genome‐wide association studies in European and Japanese populations reported on new loci for diabetic kidney disease (DKD), including FTO. In this study, we have replicated these investigations on a cohort of 410 Type 2 diabetes mellitus (T2DM) patients of Arab origin from the United Arab Emirates (UAE).Methods and ResultsThe cohort included 145 diabetic patients diagnosed with DKD and 265 diabetics free of the disease. In general, we were able to confirm the association between the FTO locus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These findings indicate a relevant relationship between the rs7204609 polymorphism and CKD, which, to the best of our knowledge, has not been reported previously. Studies in Czech, Japanese, and Emirati populations have demonstrated a relationship between CKD and FTO variants – rs17817449, rs56094641, and both rs1421086 and rs17817449 polymorphisms, respectively [10-12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate a relevant relationship between the rs7204609 polymorphism and CKD, which, to the best of our knowledge, has not been reported previously. Studies in Czech, Japanese, and Emirati populations have demonstrated a relationship between CKD and FTO variants – rs17817449, rs56094641, and both rs1421086 and rs17817449 polymorphisms, respectively [10-12].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, genome-wide association studies have identified an association between polymorphisms of the fat mass and obesity-associated ( FTO ) gene and T2D in several populations [9], as well as associations with CKD [10-12]. The FTO gene is located on the long arm of the Chromosome 16 on the position 12.2 and consists of 9 exons, occupying an area of >400 kb [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in United Arab Emirates (UAE) about genomic medicine [32-36]. Nevertheless, no studies about mapping the power, interest, and the attitude of the various stakeholders in the UAE pertaining to the implementation of genomic medicine and pharmacogenomics have been conducted.…”
Section: Introductionmentioning
confidence: 99%